2019
DOI: 10.1007/s00114-019-1621-1
|View full text |Cite
|
Sign up to set email alerts
|

Changes in prolactin, cortisol and testosterone concentrations during queen succession in a colony of naked mole-rats (Heterocephalus glaber): a case study

Abstract: Changes in prolactin, cortisol and testosterone concentrations during queen succession in a colony of naked mole-rats (Heterocephalus glaber): a case study. The Science of Nature 106: 26.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 24 publications
1
37
1
Order By: Relevance
“…We found no linear effect of social rank on working behaviour, but did find an effect of rank-squared. Naked mole-rat groups have strict dominance hierarchies ( Clarke & Faulkes, 1997 ) and periods with high rates of aggression and fighting during which individuals are often killed ( Clarke & Faulkes, 1997 ; Clarke & Faulkes, 2001 ; Medger et al, 2019 ). High-ranking naked mole-rats are more likely to become breeders if the previous breeders are removed ( Clarke & Faulkes, 1997 ; Clarke & Faulkes, 1998 ), and may reduce energy spent on working behaviour in order to prepare for future dominance challenges.…”
Section: Discussionmentioning
confidence: 99%
“…We found no linear effect of social rank on working behaviour, but did find an effect of rank-squared. Naked mole-rat groups have strict dominance hierarchies ( Clarke & Faulkes, 1997 ) and periods with high rates of aggression and fighting during which individuals are often killed ( Clarke & Faulkes, 1997 ; Clarke & Faulkes, 2001 ; Medger et al, 2019 ). High-ranking naked mole-rats are more likely to become breeders if the previous breeders are removed ( Clarke & Faulkes, 1997 ; Clarke & Faulkes, 1998 ), and may reduce energy spent on working behaviour in order to prepare for future dominance challenges.…”
Section: Discussionmentioning
confidence: 99%
“…For example, female naked mole-rats competing for dominant breeding status following removal of their queen show increases in both cortisol and progesterone (Clarke and Faulkes, 1997). In a recent case study of queen succession in naked mole-rats (Medger et al, 2019), the new queen showed mating behavior indicating reproductive activation, yet had cortisol levels that were very high (~90 ng/ml) when still in olfactory contact with the original queen. Cortisol levels then dropped to ~40 ng/ml after the original queen was completely removed.…”
Section: Stress and Reproductive Suppressionmentioning
confidence: 99%
“…Subordinates in this particular colony had increased cortisol following queen removal and this was also the only colony in which more than one female tried to take over breeding status. Medger et al (2019) reported that plasma cortisol was approximately 70 ng/ml in subordinates after queen removal and during a period of fighting, with levels decreasing to approximately 40-45 ng/ml after the new queen was established. This pattern of results might reflect colony variation in social stability where no relationship between cortisol and status is seen in stable colonies but cortisol increases in animals anticipating or participating in competition for dominant breeding status.…”
Section: Social Status and Colony Stabilitymentioning
confidence: 99%
“…The remaining colony members are non-reproductive [non-breeding females (NBFs); non-breeding males (NBMs)] and are reproductively quiescent, where non-reproductive members can reproduce but are socially reproductively suppressed by the dominant breeding individuals (Bennett and Faulkes, 2000). This reproductive suppression can be physiological (Bennett et al, 2018;Medger et al, 2019;Blecher et al, 2020) or behavioural (e.g., incest avoidance) (Burda et al, 1990;Bennett et al, 1996Bennett et al, , 1997Lutermann et al, 2013) or even the two in unison (Bennett et al, 1996). Non-breeding colony members dispersal from their natal colonies during periods of high rainfall when the soil characteristics are optimal for excavation and digging (Jarvis et al, 1994;Molteno and Bennett, 2002;Scantlebury et al, 2006).…”
Section: Introductionmentioning
confidence: 99%